Pengembangan Instrumen Penilaian Berbasis Pendidikan Multikultural pada Muatan Pelajaran Bahasa Indonesia Tema Persatuan dalam Perbedaan Kelas VI Sekolah Dasar - Ani Satul Inajati; Ngatmini Ngatmini; Asrofah Asrofah (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2023)
The purpose of this study was to produce an assessment instrument based on multicultural education on the Indonesian language subject matter, the theme of Unity in Differences for grade VI elementary schools that is feasible (valid, practical and effective) to improve the quality of processes and learning outcomes for grade VI elementary school students. This research is research development (R & D) which refers to the theory of Borg and Gall. Limited trials were conducted in class VI with 3 (three) elementary schools, namely SD N Pedurungan Kidul 02, SD N Pedurungan Kidul 05, and SD Muhammadiyah 08 Semarang.. Limited trial using one group pretest-posttest design. Methods of data collection using observation techniques, test techniques and questionnaires to obtain validity results. Data analysis techniques are descriptive and quantitative. The results of the validity test of the assessment instrument were stated to be very valid with a percentage of 88.75%. The multicultural education-based assessment instrument developed is classified as practical criteria, where the results of the teacher and student responses show an assessment of 88% with very feasible criteria. The multicultural education-based assessment instrument that has been developed is effective in improving the quality of the process and learning outcomes with the theme of the beauty of togetherness with the results of the student's effectiveness test being 80% of the scores meet the kkm. The results of the study concluded that the assessment instrument based on multicultural education that was developed met the criteria of being valid, practical, and effective so that it was feasible to improve the quality of the student learning process on the theme of beautiful togetherness of civic education lesson content for grade iv elementary school.